2017
DOI: 10.1016/j.landusepol.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

The development of highway nuisance perception

Abstract: The perception of highway nuisance i.e. noises, air pollution and barrier-effects, is associated with negative effects on health and quality of life. This study aims to gain a deeper understanding of the development of highway nuisance perception among residents. Interviews were conducted with residents in 32 households living along the Southern Ring Road, a highway which crosses various neighbourhoods in the city of Groningen, the Netherlands.Various themes emerged from the interviews which were important in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…People living in a greener neighborhood or perceiving it as greener were found to perceive lower noise annoyance. This result was confirmed by other studies [26,30,45,49]. In particular, Li at al.…”
Section: Factors Influencing the Acoustic Perception Of Indoor Residesupporting
confidence: 88%
See 3 more Smart Citations
“…People living in a greener neighborhood or perceiving it as greener were found to perceive lower noise annoyance. This result was confirmed by other studies [26,30,45,49]. In particular, Li at al.…”
Section: Factors Influencing the Acoustic Perception Of Indoor Residesupporting
confidence: 88%
“…No trend towards higher road traffic annoyance with longer residence periods was found by Riedel et al [26]. Interviews by Hamersma et al reported that in several cases the perception of nuisance at home caused by an highway decreased with increased time of residence, as residents got used to it [30]. Differently, Babisch et al found no habituation effect for people who had lived longer in their dwellings, that, on the contrary, showed a stronger increase of annoyance at increasing road traffic noise levels [15].…”
Section: Factors Influencing the Acoustic Perception Of Indoor Residementioning
confidence: 93%
See 2 more Smart Citations
“…To abide by ethical considerations we informed all residents about the general purpose of the study, the research team, the handling of data, and the duration of the interview. We assured them that participation was voluntary, we gave them the option to withdraw from the interview at any time and to read the transcripts afterwards, and we requested that they sign a letter of consent (Hamersma et al 2017). Figure 2 gives an overview of the geographical location of our interviewees, and Table 2 provides their background information.…”
Section: Preferred Level Of Involvement (Residents' Perspective)mentioning
confidence: 99%